A Sharing of Voices - Willson, Michele (Legge Gallery, 2009)
Technology is increasingly used to mediate our relationships with one another as well as our way of gaining information about the world we live in. It is used to make sense of the world we live in increasingly complex ways that theory still has been unable to adequately encapsulate. The essay articulates the ways in which communication technology acts as both an intermediary and as a source of information in our relationships and in our emotional lives, and how this impacts on our ways of making sense of the world. It points to an alternate way of understanding and expressing this relationship in writing and in art across time and space in the exhibition by Annette Iggulden, “Breath and Stones”.